Subspecies limits and hidden Wolbachia diversity in Actinote pellenea butterflies. Issue 8 (17th November 2021) - Silva-Brandão, Karina L.; Cirino, Mariana; Magaldi, Luiza De Moraes; Gueratto, Patrícia Eyng; Mattos, Ricardo Gabriel; Freitas, André V. L.
Abstract : Actinote pellenea is the most widespread species within the genus Actinote (Lepidoptera: Nymphalidae: Heliconiinae: Acraeini). The species has several generations per year (multivoltine) and is also the most diversified, with 18 formally recognized subspecies, most of them morphologically distinct and geographically segregated. In the present study we investigated lineage limits of 12 subspecies of A. pellenea using sequences of one mitochondrial (COI) and one nuclear gene (EF-1 α) to test if nominal geographic lineages are recovered as genetically differentiated. We also surveyed for the presence of Wolbachia in all field-collected individuals of A. pellenea and characterized these bacteria using sequences of wsp and gatB. The analysis of the COI alignment failed to recover all subspecies as monophyletic and only the clade composed for A. pellenea diaguita from Tucumán, Argentina and A. pellenea pellenea from the coastal Atlantic Forest in the states of São Paulo and Bahia, Brazil, was differentiated as a separate lineage. We found a Wolbachia -infection frequency of 68%, in both males and females, and we propose that the presence of these endosymbionts may explain why the mitochondrial gene COI failed to delimit the subspecies of A. pellenea as monophyletic groups. We showed for the first time that these butterflies have an intermediate prevalence of Wolbachia infection. However, several aspects of this infection are still unknown and we concluded the present study with several open questions relative to the interaction between Wolbachia and A. pellenea butterflies.